Optic Neuritis Caused by Rathke’s Cleft Cyst in Young Adult - Namie Kobayashi; Toshiyuki Oshitari; Kentaro Kobayashi; Takatsugu Onoda; Hidetoshi Ikeda; Emiko Adachi-Usami (Case Reports in Ophthalmological Medicine)
We report a case of right optic neuritis caused by Rathke's cleft cyst (RCC) in a young adult. A 15-year-old boy presented with reduced visual acuity in the right eye. He was diagnosed with optic neuritis in the right eye 4 years earlier at other clinics before he was referred to our department. During our one-year examinations, the cause of the reduced vision in his right eye could not be determined conclusively. At the age of 17 years, a RCC was detected by a neurosurgeon who specialized in hypophyseal diseases. He underwent microscopic transsphenoidal resection of the cyst, and his vision recovered to 1.2 and he has had no recurrence for at least 9 months. We suggest that repeated rupturing of the RCC was the cause of the optic neuritis, and a RCC can be successfully treated by surgery even after 3 years of optic neuritis.